The real Japan - McGinty, Winsor T. (The Japan Times, 1992)
In this haunting study of one of asia's least-visited countries, the author makes extensive use of existing travel guides to piece together a description of contemporary Mongolia for which could have been responsible. Some critics felt had McGinty actually visisted Mongolia.